AB0154 Notch3 is upregulated in lupus nephritis and its deficiency accelerates lupus progression. (12th June 2018) - Breitkopf, D.; Hermert, D.; Groene, E.; Martin, I.; Floege, J.; Ostendorf, T.; Raffetseder, U.; Rauen, T.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory disease that affects the kidneys in about 50% of patients. Lupus nephritis (LN) is a major risk factor for overall morbidity and mortality in SLE patients. Notch signaling constitutes an evolutionarily conserved pathway that determines major decisions in cell proliferation, survival, and differentiation. Objectives: To address the role of Notch-3 signalling in the disease development of SLE and particularly LN. Methods: We measured renal expression of Notch-3 in kidneys of both, LN patients and lupus-prone MRL. lpr mice. Notch-3 -/- and B6. Fas lpr/lpr mice were crossbred to generate a B6. Fas lpr/lpr Notch-3 -/- genotype and we analyzed the spontaneous disease manifestations in 40 week-old mice. Furthermore, we administered antisense oligodeoxynucleotides (ODNs) targeting Notch-3 or scrambled controls in the more aggressive lupus-prone mice strain (MRL. Fas lpr/lp ) mice starting at week 12 for 3 weeks and analyzed these mice at the age of 16 weeks. Results: In 20-week old MRL. lpr mice, receptor Notch-3 and its target gene Hes2 were significantly up-regulated in kidneys in comparison to 8 and 12 week-old littermates. De novo renal Notch-3 expression in lupus mice and SLE patients was especially pronounced in the glomerular compartment. B6. Fas lpr/lpr Notch-3 -/- mice exhibited an aggravated lupus phenotype with earlier mortality, increased lymph nodes/spleen size, enhanced glomerular collagen IV deposition and increased immune cell infiltration in the kidneys. In line with this, application of anti-sense Notch-3 ODNs in MRL. lpr mice at the time of the transition from clinically inapparent to a manifested disease state (starting at week 12), resulted in accelerated disease progression as evidenced by enhanced lymphadenopathy, splenomegaly and an increase of inflammatory markers Conclusions: Overall, these results demonstrate that Notch-3 exerts protective effects in the course of SLE, and its deficiency or inhibition accelerates the development of SLE manifestations. Disclosure of Interest: None declared